Dinoflagellate cyst assemblages of the Cunga - Quifangondo cenozoic formations in the Cabo São Brás section, Kwanza Basin (Angola): towards a first stratigraphic and paleoenvironmental interpretation - Pereira, Zélia (2021)
ABSTRACT: This work introduces one of the first palynostatigraphic study conducted on formations from the Eocene and overlying lowermost Miocene successions (Cunga and Quifangondo formations) exposed in the Onshore Kwanza Basin, Angola. To improve the Cunga and Quifangondo formations age, new biostratigraphic correlations and palaeoenvironmental interpretations based on qualitative and quantitative analyses of organic walled dinoflagellate cysts from sedimentary rocks sampled in the Cabo de Sao Bras section were obtained. Those works have revealed that the Cunga Formation could be assigned to a middle Eocene - early Oligocene age, with a palynomorph signature typical of outer neritic to oceanic environments (dominance of dinocysts with microforaminiferal linings and radiolarian pyritized fragments). The lower Quifangondo Formation could be assigned to late Oligocene (latest Chattian) - early Miocene (Aquitanian) ages. This assumption is based on the first occurrence of Ectosphaeropsis burdigalensis, and the last occurrence of Deflandrea spp. and Chiropteridium galea. Additionally, the Chiropteridium, Distatodinium, Homotryblium, Hystrichokolpoma and Lingulodinium acme endorses a latest Chattian-early Aquitanian age to these samples. The palynomorph signature of this unit reflects an outer neritic environment. The latest Oligocene/early Miocene Quifangondo Formation overlaps unconformably on strata of the middle Eocene to early Oligocene Cunga Formation, pointing out a hiatus between the two units.